When I Hate to Follow You: Hate-Following, Envy, and Schadenfreude on Instagram - Yusainy, Cleoputri; Adila, Isma; Kusumastuti, Ayu; Hikmiah, Ziadatul; Faradisa, Koesrina Rahma; Valentinovich, Konstantinov Vsevolod (Faculty of Psychology, Universitas Gadjah Mada, 2023)
Popular media has documented an increasing interest in the phenomenon of “hate-following”. The current study explored the utility of hate-following motive, independent of hate, within the framework of dual approach of envy and schadenfreude. Undergraduate Instagram’s users (n = 560, 73.39% females; M age =21.14, SD = 2.04) were asked to recall an envy episode and filled in measures of state envy, hate-following motive, and hate, then read a schadenfreude scenario and completed measure of schadenfreude. We found that both hate-following motive and hate were positively associated with pain of envy, malicious envy, and schadenfreude, but only hate-following motive positively associated with benign envy. While the hate-followers experiences of malicious envy predicted higher schadenfreude, the presence of benign envy predicted lower schadenfreude. These findings highlight the unique contribution of hate-following motive, while at the same time open up many questions as to how this antisocial but nevertheless functional motive may be improved.